2017
DOI: 10.1051/0004-6361/201629968
|View full text |Cite
|
Sign up to set email alerts
|

SN 2015bh: NGC 2770’s 4th supernova or a luminous blue variable on its way to a Wolf-Rayet star?

Abstract: Very massive stars in the final phases of their lives often show unpredictable outbursts that can mimic supernovae, so-called, "SN impostors", but the distinction is not always straightforward. Here we present observations of a luminous blue variable (LBV) in NGC 2770 in outburst over more than 20 yr that experienced a possible terminal explosion as type IIn SN in 2015, named SN 2015bh. This possible SN (or "main event") had a precursor peaking ∼40 days before maximum. The total energy release of the main even… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 130 publications
5
101
3
Order By: Relevance
“…This is especially true when we consider that the F606W image of the progenitor included Hα emission, while the more recent F555W image does not. In a preliminary report of groundbased photometry, Thoene et al (2015) also reported that SN 2009ip continued to fade, and by a few months after our HST images were taken, it was reported to be fainter than the progenitor.…”
Section: Sn 2009ip Late-time Photometrymentioning
confidence: 76%
“…This is especially true when we consider that the F606W image of the progenitor included Hα emission, while the more recent F555W image does not. In a preliminary report of groundbased photometry, Thoene et al (2015) also reported that SN 2009ip continued to fade, and by a few months after our HST images were taken, it was reported to be fainter than the progenitor.…”
Section: Sn 2009ip Late-time Photometrymentioning
confidence: 76%
“…More violent ejection events are observed in massive stars surrounded by low excitation nebulosities (e.g., the canonical luminous blue variable AG Carinae, Thackeray 1977, or the P-Cygni star itself). They have generally lower expansion velocities than those of V404 Cyg (e.g., P-Cyg ∼ 200 km s −1 , Smith & Hartigan 2006), but there have been reports of outflows as fast as 2000 km s −1 (see Thöne et al 2017). All these similarities led MD16 to describe this phase of the V404 Cyg outburst as the nebular phase.…”
Section: June 2015mentioning
confidence: 99%
“…If the star is obscured by a significant mass of CSM, then an optically thick, Hα-emitting wind could explain the timescale of variability. Assuming a wind Thöne et al 2017). We indicate dotted lines for the F 350LP magnitudes during the "high" state and "low" state as discussed in Section 3.3.1.…”
Section: Pre-outburst "Flickering"mentioning
confidence: 99%
“…Many of these SN impostors have pre-outburst detections, which suggests their progenitor systems contain very massive stars. Given the luminosity, colours, and pre-outburst variability of these sources, several historical and recent SN impostors are thought to come from luminous blue variable (LBV) stars, includ-ing SN 1954J (Tammann & Sandage 1968), SN 1997bs (Van Dyk et al 2000, SN 2000ch (Wagner et al 2004;Pastorello et al 2010), SN 2002kg (Weis & Bomans 2005;Maund et al 2006), SN 2008S (Smith et al 2009), SN 2009ip and UGC2773-OT Foley et al 2011), SN 2015bh (also known as SNHunt 275 and PTF13efv; Ofek et al 2016;Elias-Rosa et al 2016;Thöne et al 2017), and PSN J09132750+7627410 (Tartaglia et al 2016). Light echoes from the Galactic LBV η Car indicate that many SN impostors are spectroscopically similar to the nonterminal great eruption of that star in the 1830s, which ejected a massive, bipolar nebula of circumstellar material (CSM) but left a surviving star .…”
Section: Introductionmentioning
confidence: 99%